Family Coping Strategies and Quality of Life of Patients with Type-2 Diabetes Mellitus in Primary Health Care in Indonesia - Setyoadi Setyoadi; Ferry Efendi; Joni Haryanto; Fitri Rosyidawati; Niko Dima Kristianingrum; Yati Srihayati; Dina Dewi Sartika Lestari Ismail (Nurse Media: Journal of Nursing)
Background: The intricate caregiving responsibilities undertaken by family caregivers in the care of patients with chronic diseases induce stress, potentially reducing the family’s ability to provide effective care. In instances where family caregivers of patients with type-2 diabetes mellitus (T2DM) are unable to employ effective coping mechanisms, there exists the potential for an adverse impact on the patient’s quality of life.